IgE and eosinophil cationic protein (ECP) as markers of severity in the diagnosis of atopic keratoconjunctivitis - Wakamatsu, Tais H; Satake, Yoshiyuki; Igarashi, Ayako; Dogru, Murat; Ibrahim, Osama M A; Okada, Naoko; Fukagawa, Kazumi; Shimazaki, Jun; Fujishima, Hiroshi (British journal of ophthalmology, 2012)
AimsTo evaluate tear and serum IgE and eosinophil cationic protein (ECP) as severity markers for atopic keratoconjunctivitis (AKC).MethodsThirty eyes of 30 patients with AKC and 10 eyes of 10 healthy control subjects were examined in this prospective study. All subjects underwent fluorescein staining, conjunctival injection, conjunctival oedema and papillary formation grading. Tear and serum IgE and ECP levels were measured, and correlations between them investigated with reference to the ocular surface clinical parameters.ResultsThe mean fluorescein scores, conjunctival injection, oedema scores and papillary formation were significantly higher in AKC patients compared to controls (p<0.05). Higher total IgE and ECP levels were detected in AKC tears compared with the control group. Tear ECP levels showed a significant correlation with fluorescein staining, conjunctival injection and oedema scores (r=0.70, 0.62 and 0.62, respectively). Tear IgE had no correlation with clinical signs. Serum IgE and ECP levels were elevated in AKC patients but did not show any correlation with clinical signs.ConclusionThis study suggests the presence of an eosinophilic response in AKC disease independent of IgE sensitisation. Tear ECP was a useful marker delineating the severity of ocular surface disease in AKC.